Total pancreaticoduodenectomy with autologous islet transplantation 14 years after liver‐contained composite visceral transplantation. Issue 8 (14th May 2018) - Nassar, Ahmed; Quintini, Cristiano; Costa, Guilherme; Lennon, Elizabeth; Bottino, Rita; Hatipoglu, Betul; Hashimoto, Koji; Fujiki, Masato; Kandeel, Fouad; Walsh, R. Matthew; Abu‐Elmagd, Kareem
Abstract: Chronic pancreatitis (CP) is a severely disabling disorder with potential detrimental effects on quality of life, gut function, and glucose homeostasis. Disease progression often results in irreversible morphological and functional abnormalities with development of chronic pain, mechanical obstruction, and pancreatic insufficiency. Along with comprehensive medical management, the concept of total pancreatectomy and islet autotransplantation (TP‐AIT) was introduced 40 years ago for patients with intractable pain and preserved beta‐cell function. With anticipated technical difficulties, total excision of the inflamed‐disfigured gland is expected to alleviate the incapacitating visceral pain and correct other associated abdominal pathology. With retrieval of sufficient islet‐cell mass, the autologous transplant procedure has the potential to maintain an euglycemic state without exogenous insulin requirement. The reported herein case of CP‐induced recalcitrant pain and foregut obstruction is exceptional because of the technical challenges in performing native pancreaticoduodenectomy in close proximity to the composite visceral allograft with complex vascular and gut reconstructions. Equally novel is transplanting the auto‐islets in the liver‐contained visceral allograft. Despite intravenous nutrition shortly after birth, liver transplantation at age 13, retransplantation with liver‐contained visceral allograft at age 17 and TP‐AIT at age 31, the 38‐year‐old recipient is currently pain free with full nutritional autonomy and normal glucose homeostasis. Abstract : A total pancreaticoduodenectomy with autologous islet transplantation in a liver‐contained composite visceral transplantation results in complete insulin independence posttransplantation.